Norbert Elías y la teoría del símbolo - Valencia Gutiérrez, Alberto (Sociedad y Economía, 2004)
The paper aims to present the main ideas of the book Theory of Symbols by German sociologist and philosopher Norbert Elias using as strategy the way in which a series of oppositions are proposed and developed: biology and sociology, materialism and idealism, biological and social evolution, animal and human language, the social and organic elements of the language development. The goal is to appreciate the contribution of Elias to the construction of a modern theory of the symbol. through the transformation of a theory of knowledge into a sociology of knowledge.